PERFORMING A PRESENT FROM THE PAST : The Värmland heritage gift, materialized emotions and cultural connectivity - Gradén, Lizette (Ethnologia Europaea, 2010)
Drawing on actor-network theory and theories of performance, this article discusses gift-giving as an expansive form of materializing relationships and delimiting boundaries between nations, regions, organizations and individuals in the wake of migration. Initially, I discuss gift-giving as a way of materializing relationships and building networks. Thereafter, I map out the social life of the Värmland Gift to America, a collection donated by the Värmland province in Sweden to the American Swedish Institute in Minneapolis in 1952. I suggest the coinage of heritage gift as a term to describe gifts with dense biographies which contain and enact multiple performances that simultaneously create and recreate the idea of gift-giving in its role as an activity that binds people together. The analysis of the Värmland Gift shows how such a heritage gift kept on the move over time involves not one but a series of performances which have fostered dynamic transatlantic relationships for over fifty years.
Keywords: Emigration; Gift-giving; Heritage gift; Performance; Transnational relationships